Episodes of urinary tract infection in post-renal transplant patients based on count regression models.. - Nieto, Xandro Alexi A. (University of the Philippines, 2016)
Abstract (Renal transplant has been one of the best options in patients with end-stage renal disease. However, this option can lead to urinary tract infections, which can lead to hemorrhage, impaired graft function, graft failure and even death. Data were gathered from the renal transplant procedures performed in National Kidney and Transplant Institute (NKTI) from 2012 to 2014. Results showed that, using zero-inflated Poisson regression, male post renal transplant patients have incidence risk ration of UTI lower by 0.52 [IRR = 0.48; 95% CI: 0.26 to 0.88], and patients who had chronic glomerulonephritis have lower UTI incidence risk ration by 0.66 [IRR = 0.34; 95% CI: 0.22 to 0.52]. Furthermore, the odds ration that hypertensive nephrosclerosis patients will not have UTI is 2.32 [OR = 1.04; 95% CI: 1.06 to 5.043]).